PELATIHAN PENGGUNAAN INTERNET UNTUK PENELUSURAN SUMBER INFORMASI BAGI MURID SIT AZKIA DEPOK: PELATIHAN PENGGUNAAN INTERNET UNTUK PENELUSURAN SUMBER INFORMASI BAGI MURID SIT AZKIA DEPOK - Nur Kholis Putra Nur; Muhammad Faried Ikhwan Faried; Anna Marchia Anna; Abdul Rahman Yusup; Sony Arianto Sony; Putri Esa Suciati Putri; Aryandika Putra Rhamadhan Dika; Ade Yuli Ova Balok Ova; Iqbal Samsudin Iqbal; Imam Maulana Imam (CV. Multi Kreasi Media, 2022)
The use of the internet in technology 4.0 has grown very rapidly and can even be used to do various activities online. But even so, we must be able to wisely use it because if not used properly there will be a bad impact from the search we do. For this reason, internet use training for information source search for SIT Azkia Depok students so as not to fall into bad things when surfing the internet. The method used in Community Service activities at SIT Azkia is by socializing directly with students about how to find sources of information and the use of online tools. The result of these activities is that SIT Azkia students become wiser in using the internet to find the various information needed.